STRUKTUR KOMUNITAS DAN KERAGAMAN PLANKTON ANTARA PERAIRAN LAUT DI SELATAN JAWA TIMUR, BALI DAN LOMBOK - Sachoemar, Suhendar I; Hendiarti, Nani (Jurnal Hidrosfir Indonesia, 2006)
A study of the plankton variability and their community structure in the Southern Coastal Area of East Java-Bali-Lombok was conducted to obtain the information of their characteristics and the status of microscopic marine organism in relation to the marine environment on the based of the biological observation. The results show that the marine environment ecologically was stable and productive due to the upwelling occurrencein the South East Monsoon. The plankton communities generally can be found consist of three classes of the phytoplankton (Cyanophyceae, Dinophyceae and Bacillariophyceaea) and two classes of zooplankton (Ciliata and Crustacea). There is no dominance of certain plankton in the observation area and the distribution among the species are relatively proportional.